Moment Inequalities and Their Application. Issue 1 (January 2015) - Pakes, A.; Porter, J.; Ho, Kate; Ishii, Joy
<x xml:space="preserve">Abstract</x> This paper provides conditions under which the inequality constraints generated by either single agent optimizing behavior or the best response condition of multiple agent problems can be used as a basis for estimation and inference. An application illustrates how the use of these inequality constraints can simplify the analysis of complex behavioral models.